A longitudinal study of cognitive decline in rural Tanzania: rates and potentially modifiable risk factors. (21st March 2018) - Heward, Jessica; Stone, Lydia; Paddick, Stella-Maria; Mkenda, Sarah; Gray, William K.; Dotchin, Catherine L.; Kissima, John; Collingwood, Cecilia; Swai, Bernadetha; Walker, Richard W.
ABSTRACT: Background: The number of people living with dementia in sub-Saharan Africa (SSA) is expected to increase rapidly in the coming decades. However, our understanding of how best to reduce dementia risk in the population is very limited. As a first step in developing intervention strategies to manage dementia risk in this setting, we investigated rates of cognitive decline in a rural population in Tanzania and attempted to identify associated factors. Methods: The study was conducted in the rural Hai district of northern Tanzania. In 2014, community-dwelling people aged 65 years and over living in six villages were invited to take part in a cognitive screening program. All participants from four of the six villages were followed-up at two years and cognitive function re-tested. At baseline and follow-up, participants were assessed for functional disability, hypertension, and grip strength (as a measure of frailty). At follow-up, additional assessments of visual acuity, hearing impairment, tobacco and alcohol consumption, and clinical assessment for stroke were completed. Results: Baseline and follow-up data were available for 327 people. Fifty people had significant cognitive decline at two-year follow-up. Having no formal education, low grip strength at baseline, being female and having depression at follow-up were independently associated with cognitive decline. Conclusions: This is one of the first studies of cognitive decline conducted in SSA. Rates of decline at two years were relatively high. Future work should focus on identification of specific modifiable risk factors for cognitive decline with a view to developing culturally appropriate interventions.